The effect of two types of tapering on plasma anabolic and catabolic steroid hormones following incremental training in elite male wrestlers - Karimi, M.; Nik Bakht, H.; Vaez Musavi, M. K. (International Journal of Wrestling Science, 2011)
The purpose of the present study was to determine the effect of two types of tapering on the concentration of plasma testosterone (T), cortisol (C) and testosterone to cortisol (T:C) ratio in elite male wrestlers after a period of incremental training. Thirty elite male wrestlers were selected randomly and divided into three equal groups: tapering 1 (50% reduction in training volume), tapering 2 (75% reduction in training volume) and control (regular training). Following four weeks of incremental training, one week of tapering was performed. Blood samples were collected from all participants at the beginning of the 1st week and at the end of the 4th and 5th weeks. Plasma levels of C and T were assayed using standard commercial ELISA kits (Quantikine; R & D Systems, Minneapolis, MN). Data were analyzed by using one-way ANOVA. The results showed that after one week of tapering, the plasma levels of C significantly decreased (P>0.05). Despite increases in plasma levels of T, it was not statistically significant. However the T:C ratio increased (P> 0.05). The results indicate that both types of tapering might improve physical performance and alter anabolic and catabolic steroid hormones in elite male wrestlers, but the 75% reduction in training volume, while the intensity is kept high, has the most beneficial effect on anabolic and catabolic steroid hormones in wrestlers.